Penerapan Prinsip Arsitektur Bioklimatik Pada Pusat Pelatihan Bola Voli Di Tembilahan - Tri Handayani; Yohannes Firzal; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Charismatic is the science of architecture concerned with the lokal wildlife potential and the complexity of the environment. The milky way architecture was applied to buildings using the wind as ventilation and sunlight as natural lighting on the buildings.volleyball alon is one of the most popular sporting branches in the neighborhood and childern. The lack of government attention as well as the absence of the training vassels will be the leading cause of the volleyball in the batting went down having facilities and containers that would support the training activities could enhance the performance of the volleyball in the tempo.To get comfortable training centers for people who will do training are selected concept the comfort of a local stream that takes care of the comfort of a athlete and potential in the sequenced environment firs the bioclimatic approach.Keywords: Bioclimatic Architecture, Volleyball